An Empirical Look into Inflation Dynamics through Real and Financial Sector Lenses for Emerging Market Economies - Capazario, Michélé (My University, 2018)
I estimate six equations already posited within the literature that aim to measure inflation and its relation to various factors from both the standpoint of the real portion and the financial portion of the economy. Therefrom, I develop and estimate a model addressing issues found in the literature around the impact that globalization has on the inflation process. All seven model specifications are treated with two sorts of expectation decomposition- that found in the methodology outlined by Pindyck and Rubinfeld (1998) and that adapted from Kalman (1960). This is undertaken for Israel, South Korea, Mexico and South Africa- a handful of emerging market economies. Treating all estimations thusly, a few stylized facts need to be brought to light; firstly, the new model posited by this paper (the Trade –Seigniorage synthesis) appears a robust way in which to map inflation while controlling for the impact that globalization and world income growth might have on its (inflation’s) movement across time. Furthermore, contra the position held by Fama (1981), this research has pointed out that- for these particular emerging markets- models rooted in the real portion of the economy are, on average, more robust in digesting information, and may thus lead to mapping inflation expectations with more accuracy than models rooted in the financial sector of the economy. Finally, it could be argued that- although both inflation expectation decompositions have their respective flaws- inflation expectations in these emerging markets need not be perfectly rational (focusing on all information within the dataset), but instead imperfectly rational (instead, more accurate expectations are governed by only a limited memory of data within the dataset).
Michélé Capazario, Masters, 732220 ,2018